Princess lessons - Pearl, Alexa, 1967-; Sordo, Paco (New York, NY : Little Bee Books, 2017)
After learning that she is the princess of the flying horses, Sasha must pass a difficult princess test before she can attend to her royal duties.
2.9
K-3
590L
Keywords: Horses -- Juvenile fiction; Animals, Mythical -- Juvenile fiction; Princesses -- Juvenile fiction; Examinations -- Juvenile fiction; Horses -- Fiction; Animals, Mythical -- Fiction; Princesses -- Fiction; Examinations -- Fiction; Fantasy fiction